Textual dimensions in contemporary narrative discourse: the novel of the chaos of the senses as a model - Jumaa, Roaa (Al-Adab Journal, 2025)
The importance of narrative discourse is evident in the fact that it is not just a discourse programmed according to the linguistic dimensions that are employed according to the context of the maqam, but its importance appears as a multi-dimensional semantic, contextual and ideological discourse, emanating from a shady reality, unclear dimensions. Hence the fact that the narrative text presents to the reader of several concepts that help him understand human history and the lived present. The research shows the study of the manifestations of textual dimensions in the novel Chaos of the Senses by Ahlam Mosteghanemi, taking the concept of pilgrims and intentionality as important dimensions that exist within each literary text that carries a cultural discourse.